Analisis Penyusunan Laporan Keuangan Berdasarkan SAK EMKM Menggunakan Aplikasi Keuangan Berbasis Android SI APIK - Dina Arista Prihatin; Arisky Andrinaldo; Indrawati Mara Kesuma; Martini Martini; Weni Susanti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study is to determine the Analysis of the Preparation of Financial Statements Based on SAK EMKM in the Implementation of the APIK SI Financial Application at the Tempe Cipto Roso Factory, Megang Sakti District. The type of research used is descriptive research with qualitative data analysis using primary data sources and secondary data sources. Agency theory is a reference in this research theory that explains the working relationship between company owners and company management. The results of this application are financial reports such as balance sheets, cash flow statements and income statements. In addition, this application can accurately describe the company's financial status.